2013
DOI: 10.1103/physrevc.87.054324
|View full text |Cite
|
Sign up to set email alerts
|

New nuclear structure features in transactinide nuclei

Abstract: The structural evolution of the heavy nuclei, with Z > 82, is investigated by looking at the differential variation of the two-neutron separation energies. It indicates, by non-monotonous behavior at certain neutron numbers, structure phenomena such as major shell (N = 126) and deformed subshell (N = 152) closures. Another interesting effect is observed at N ∼ 142, which is very well correlated with a previously observed, intriguing behavior of quantities measured in alpha decay, such as relative branching rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…Alpha-decay is a prominent decay channel of heavy and superheavy nuclei (SHN) and acts as an effective probe for the nuclear structure [1][2][3][4][5][6][7][8][9][10][11]. α-decay can provide a powerful and very precise tool to identify new superheavy elements studied at accelerator centers such as Berkeley, GSI, Dubna, GANIL, and RIKEN [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-decay is a prominent decay channel of heavy and superheavy nuclei (SHN) and acts as an effective probe for the nuclear structure [1][2][3][4][5][6][7][8][9][10][11]. α-decay can provide a powerful and very precise tool to identify new superheavy elements studied at accelerator centers such as Berkeley, GSI, Dubna, GANIL, and RIKEN [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…An extension of such studies to other (strongly radioactive) targets of interest in the region discussed here is undoubtedly a very difficult task, leaving the alpha decay as the main spectroscopic tool for these nuclei. An examination of the HFs known for parent nuclei with Z 82 was recently presented by us [10]. Most of the nuclei in our set, i.e., those with mass number larger than about 220, present collective features.…”
mentioning
confidence: 99%
“…In Ref. [10] it was argued that these VCS representations should be useful for the HF values because these are quantities that depend only on the nuclear structure. Indeed, it was found that the VCS representations display much more compact trajectories for the HF values, than, e.g., the usual representation as a function of the mass number A [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies with increasing particle numbers investigate the so-called "island of stability" [6], where features like the continuing decrease of energy gaps [7] and the emergence of shape coexistence [8] have a crucial impact on the predicted position and localization of stability regions and the corresponding lifetimes of the nuclei. Although the first experimental evidence for SHN has reached the region of the predicted subshell closure at N ¼ 162 [9-11], the deformed shell closure at N ¼ 152 for transfermium nuclei (see, e.g., [12]) and, as recently pointed out, weaker shell effects in the vicinity [13], still represents the cutting edge for thorough experimental investigations. The transfermium nuclei, however, can be produced only online, in heavy-ion fusion and nucleon transfer reactions, and consequently only low yields are available for study, necessitating highly efficient techniques.…”
mentioning
confidence: 99%